Identifying pathways for large-scale implementation of a school-based mental health programme in the Eastern Mediterranean Region: a theory-driven approach. (6th November 2020) - Alonge, Olakunle; Chiumento, Anna; Hamoda, Hesham M; Gaber, Eman; Huma, Zill-e-; Abbasinejad, Maryam; Hosny, Walaa; Shakiba, Alia; Minhas, Ayesha; Saeed, Khalid; Wissow, Lawrence; Rahman, Atif
Abstract: Globally there is a substantial burden of mental health problems among children and adolescents. Task-shifting/task-sharing mental health services to non-specialists, e.g. teachers in school settings, provide a unique opportunity for the implementation of mental health interventions at scale in low- and middle-income countries (LMICs). There is scant information to guide the large-scale implementation of school-based mental health programme in LMICs. This article describes pathways for large-scale implementation of a School Mental Health Program (SMHP) in the Eastern Mediterranean Region (EMR). A collaborative learning group (CLG) comprising stakeholders involved in implementing the SMHP including policymakers, programme managers and researchers from EMR countries was established. Participants in the CLG applied the theory of change (ToC) methodology to identify sets of preconditions, assumptions and hypothesized pathways for improving the mental health outcomes of school-aged children in public schools through implementation of the SMHP. The proposed pathways were then validated through multiple regional and national ToC workshops held between January 2017 and September 2019, as the SMHP was being rolled out in three EMR countries: Egypt, Pakistan and Iran. Preconditions, strategies and programmatic/contextual adaptations that apply across these three countries were drawn from qualitative narrative summaries of programme implementation processes and facilitated discussions during biannual CLG meetings. The ToC for large-scale implementation of the SMHP in the EMR suggests that identifying national champions, formulating dedicated cross-sectoral (including the health and education sector) implementation teams, sustained policy advocacy and stakeholders engagement across multiple levels, and effective co-ordination among education and health systems especially at the local level are among the critical factors for large-scale programme implementation. The pathways described in this paper are useful for facilitating effective implementation of the SMHP at scale and provide a theory-based framework for evaluating the SMHP and similar programmes in the EMR and other LMICs.